2019
DOI: 10.1088/1755-1315/314/1/012043
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Indonesian literacy school program in improving the quality of basic education for marginal communities in the Indonesian border area

Abstract: This study aims to compile basic data, develop and implement the Indonesian School of Literacy program in Improving the Quality of Basic Education for Marginal Communities. The program aims to establish and improve school performance through a mentoring process for school principals and teachers. In addition, this program also involves parents in the learning process of students while at home. Parents are involved through parenting training held at school. The Indonesian Literacy School is a program that seeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The use of arts and projects is also assumed to have an essential role in improving educational aspect in SB. In the case of literacy, [30] who researched the effectiveness of literacy school program revealed that there was an increase in the school quality through a distinctive literacy culture. Regarding the use teaching media, [31] points out that teaching media can assist teachers in delivering materials so that the students will be easier to understand them.…”
Section: Discussion the Benefits Of Integrated International Communit...mentioning
confidence: 99%
“…The use of arts and projects is also assumed to have an essential role in improving educational aspect in SB. In the case of literacy, [30] who researched the effectiveness of literacy school program revealed that there was an increase in the school quality through a distinctive literacy culture. Regarding the use teaching media, [31] points out that teaching media can assist teachers in delivering materials so that the students will be easier to understand them.…”
Section: Discussion the Benefits Of Integrated International Communit...mentioning
confidence: 99%